Theoretical framework of school inspection effects on school - Md Ali, Nurul Jawahir; Abdul Kadir, Suhaida; Basri, Ramli; Krauss, Steven Eric (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
This paper reviews and discusses about two models of school inspection effects towards school. The models used in the discussion are Landwehr’s ‘Model of Effects and Effectiveness of School Inspection’ (2011) and ‘Framework of School Inspection Effect’ by Ehren and Visscher (2006). The first model describes the benefits of school inspection as primary instrument for gaining knowledge about school, accountability, enforcing standard and school development. This model presents the school inspection desirable outcomes at its best. The second framework on the other hand presented an elaborate concepts and variable of both school inspection effects and side effects. It describes school inspection as a process connected through features of school inspection, external impulses and support, school features, school reaction and its side effects. These models then are merged as a theoretical framework that may provide ground for future studies that wishes to study on school inspection effects on school.